Children and justice : overcoming language barriers : cooperation in interpreter-mediated questioning of minors / edited by Katalin Balogh and Heidi Salaets. - Balogh, Katalin, 1973-; Salaets, Heidi (Intersentia, 2015)
Interpreter-mediated child interviews, by their nature, involve communication with vulnerable interviewees who need extra support for three main reasons: their age (under 18), language and procedural status (victim, witness or suspect). The CO-Minor-IN/QUEST research project (JUST/2011/JPEN/AG/2961; January 2013 - December 2014) studied the interactional dynamics of interpreter-mediated child interviews during the pre-trial phase of criminal proceedings. The project aimed to provide guidance in implementing the 2012/29/EU Directive establishing minimum standards on the rights, support and protection of victims of crime. This book sets out the key findings from a survey conducted in the project partners' countries (Belgium, France, Hungary, Italy, the Netherlands and the UK) targeting the different professional groups involved in child interviewing. Both the quantitative and qualitative analysis of the respondents' answers is discussed in detail. The book also provides hands-on chapters, addressing concrete cases of children involved in criminal procedures who required the assistance of an interpreter to ensure their rights were fully protected. Finally, a set of recommendations is offered to professionals working in this area.